Anomalous small viral shells and simplest polyhedra with icosahedral symmetry: the rhombic triacontahedron case. Issue 1 (20th December 2018) - Pimonov, Vladimir V.; Konevtsova, Olga V.; Rochal, Sergey B.
Abstract : The symmetry of the capsomers forming a viral shell determines the polyhedron underlying the shell structure. If the capsid is self‐assembled from dimers, this is the rhombic triacontahedron with 30 equivalent rhombic faces. Abstract : The development of antiviral strategies requires a clear understanding of the principles that control the protein arrangements in viral shells. Considered here are those capsids that violate the paradigmatic Caspar and Klug (CK) model, and it is shown that the important structural features of such anomalous shells from the Picobirnaviridae, Flaviviridae and Leviviridae families can be revealed by models in the form of spherical icosahedral packings of equivalent rhombic structural units (SUs). These SUs are composed of protein dimers forming the investigated capsids which, as shown here, are based on the rhombic triacontahedron (RT) geometry. How to modify the original CK approach in order to make it compatible with the considered rhombic tessellations of a sphere is also discussed. Analogies between capsids self‐assembled from dimers and trimers are demonstrated. This analysis reveals the principles controlling the localization of receptor proteins (which recognize the host cell) on the capsid surface.